Reliability enhancement with dependable model predictive control. (November 2020) - Tran, Anthony Tri; Ha, Q.P.; Hunjet, Robert
Abstract: Operational Technology (OT) systems are merging towards a conjoint architecture with the advances in communication networks and emerging standards such as IEC/IEEE 60802 for industrial automation, automotive, power and energy and other areas. In this paper, we present a Dependable Control System (DepCS) with Model Predictive Control (MPC) algorithm that works in such architectures using multiple MPC controllers (of a feedback control loop) to enhance the operational reliability. We termed this as Dependable Model Predictive Control (DepMPC) system. The reliability enhancement of a DepMPC system is achievable thanks to the fault-tolerance of multiple MPC controllers and the tractable information flows with Time-Sensitive Networking (TSN). Here, our discussion was focused only on the logical connectivity and not the hardware architecture. The numerical simulations are studied with three multi-variable plants that have control constraints. In this study, we introduced a Replacement Controller (RC) to improve the control performance of the DepMPC system. The combination of both the Replacement Controller and Dependable Model Predictive Control (RC-DepMPC) system proves a promising solution for actual implementations. Graphical abstract: Highlights: Dependable Model Predictive Control (DepMPC) with a software-defined architecture for Operational Technology (OT) systems compatible with the emerging IEC/IEEE 60802 standards. Self-management of redundant controllers for smooth transferring between the standby and duty modes within a deterministic time thanks to time-sensitive networking. Replacement Controller (RC) in companion with the redundant controllers for improving the control performance of a DepMPC. Numerical simulations with three multi-variable plants and different choices of performance variables for illustration of the merits of the proposed framework.